Is there a negative judgment of taste? Disgust as the real ugliness in Kant's aesthetic (Lebenswelt. Aesthetics and philosophy of experience., 2013)
Starting from the recent debate on the role of ugly in Kant’s aesthetics and according to Paul Guyer and Reinhard Brandt, in this essay I state that in Kantian perspective any negative judgment of taste can exist. The ugly is in fact always reduced to the beauty and the principle of purposiveness doesn’t allow any pure negative aesthetic judgment. The disgust, on the contrary, seems to be the real opposite of the beauty, the irreducible ugly. In this writing I demonstrate that, with its presence, the disgust ensures the bounds of the Kantian aesthetics against the contra-purposiveness.